PROBLEMATIKA DALAM PENERJEMAHAN NOVEL - Rudi Hartono (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2012)
Translating literary works is different from translating non-literary works. One of the literary texts meant in this study is novel. In the process of translating a novel, translators sometimes have problems to determine appropriate equivalent words. The equivalent words themselves must be literary words that are difficult to search. There are many factors that cause translators difficult to translate a novel. Some of them are lack of basic knowledge of English language and literature, misinterpretation and being careless in translation process. Consequently they have difficulties in linguistics, analysis, culture, and appreciation. So the way to overcome the problems is increasing the knowledge of both languages and cultures, having literary studies background, referring to guidance and rules of translating a novel or other literary works.